Exogenous foliar ascorbic acid applications enhance salt-stress tolerance in peanut plants throughout an increase in the activity of major antioxidant enzymes - Alves, Rita de Cássia [UNESP]; Oliveira, Kevein Ruas [UNESP]; Lúcio, José Clebson Barbosa [UNESP]; Silva, Jeferson dos Santos [UNESP]; Carrega, Willians César [UNESP]; Queiroz, Samira Furtado [UNESP]; Gratão, Priscila Lupino [UNESP] (Elsevier, 2022)
Although ascorbic acid (AsA) is an antioxidant that can protect plants from oxidative damages, little is known about physiological and biochemical responses of exogenous AsA-regulated antioxidant systems to stressful-conditions in peanut plants. This study aimed to evaluate the effects of AsA-foliar applications on antioxidant defense responses in peanut plants irrigated with saline water. The experiment was carried out in a completely randomized design with four treatments formed by combining and not AsA under salt-stressful conditions (control, 50 mM AsA, 50 mM NaCl and 50 mM NaCl + 50 mM AsA). AsA application was performed twice a week spraying plant shoot. After a period of 40 days post germination, plants were collected and evaluated for the following parameters: total chlorophyll and carotenoids contents; dry biomass; malondialdehyde (MDA) and H2O2 contents, superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX), glutathione peroxidase (GSH-Px) and glutathione reductase (GR). AsA increased total chlorophyll and carotenoid contents, reduced Na+concentration, and oxidative damages by modifying antioxidant defense systems. Therefore, the exogenous application of AsA is an efficient strategy to withstand or avoid stress imposed by salt, which can be attributed to increased SOD, CAT, APX, GSH-Px and GR activities in peanut plants, and enhance salt tolerance.
Keywords: Arachis hypogea l.; Oxidative stress; Salinity